MEWUJUDKAN WORLD CLASS PROFESSIONALISM OF LIBRARIANS DI ERA LIBRARY MOBILE - Yuni Nurjanah (Central Library of Universitas Sebelas Maret, 2019)
At the century, library has offered exceptional service via mobile web users. This concept refers to the components of the mobile web - Ellyssa Kroski: users, devices, operating systems, services, content. The device not only machines, including human resources (librarian). Course professional librarians, brave move on, becoming a greater. It leads to the aspect of librarian professionalism - Steers & Porter (1991) that professional librarians are not different from other professions. Its benchmarks 1) the skills, abilities, and knowledge; 2) psychological maturity. The professionalism of thiscentury was also characterized by a global culture which is full of competition and fast-paced change. Not just the usual professionalism, but world-class professionalism that will enable us to dominate the Mobile Library and align us with other professional organizations worldwide. These has become the premise to realize a world class professionalism of librarians in the era of the mobile library. How to? These will be discussed in this article.Keywords: mobile web, web libraries, professional librarian